Scope of the 2(5H)-furanone helicity rule: A combined ECD, VCD, and DFT investigation - Dos Santos, Fernando M.; Bicalho, Keylla U. [UNESP]; Calisto, Ítalo H.; Scatena, Gabriel S.; Fernandes, João B.; Cass, Quezia B.; Batista, João M. (Royal Society of Chemistry (RSC), 2018)
One of the most widely used methods to assess the stereochemistry of chiral 2(5H)-furanones is an empirical electronic circular dichroism (ECD) helicity rule. In the present work, an extensive experimental and theoretical investigation of the scope of the above-mentioned empirical rule for acetogenins with a hydroxyl group substituted at C-4 revealed a possible exception to this rule. The underlying causes for this observation are discussed with respect to side chain substitutions, conformational requirements, chromophore handedness as well as a qualitative orbital analysis. Further investigation using vibrational circular dichroism (VCD) spectroscopy led to the identification of spectral markers that seem to be more localized and less affected by side chain substitutions. As the presence of a ϒ-lactone ring and a hydroxyl group at C-4 is a very common structural feature of Annonaceous acetogenins, we recommend the combined use of ECD and VCD spectroscopy, along with quantum chemical computations, for the stereochemical analysis of structurally related molecules.